2007
DOI: 10.1002/ange.200601780
|View full text |Cite
|
Sign up to set email alerts
|

Isolierte molekulare Drähte

Abstract: In den erstaunlich unterschiedlichen Strukturen, die bisher als “isolierte molekulare Drähte” (insulated molecular wires, IMWs) beschrieben wurden, zeigt sich, wie vielfältig die Ansätze zur elektrisch‐chemischen Isolierung auf molekularer Ebene sind. Gemeinsam verdeutlichen diese Systeme die Bedeutung von Einkapselungsstrategien bei der Entwicklung optoelektronischer Materialien und organischer Halbleiter. Dieser Aufsatz beleuchtet die Synthese und die strukturelle Charakterisierung von IMWs. Struktur‐Eigensc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 330 publications
(229 reference statements)
0
46
0
2
Order By: Relevance
“…[14c-e, 15] In addition, we previously reported that SPG complexes can show a high thermal stability; for example, the ICD signal of the SPG/PT1 complex at 90 8C still kept 80 % intensity relative to that at 20 8C.…”
Section: Induced Optical Property Changes and Circularly Polarized Emmentioning
confidence: 98%
“…[14c-e, 15] In addition, we previously reported that SPG complexes can show a high thermal stability; for example, the ICD signal of the SPG/PT1 complex at 90 8C still kept 80 % intensity relative to that at 20 8C.…”
Section: Induced Optical Property Changes and Circularly Polarized Emmentioning
confidence: 98%
“…[17] At first sight it seems surprising that the two cyclodextrin units in the [3]rotaxane 3(a-CD) 2 are localized on the end alkyne units without visiting the central alkyne, whereas in the [2]rotaxane 2a-CD the cyclodextrin hops between both alkynes. The explanation is simply that the length of an OPE repeat unit (6.9 ) is less than the length of a cyclodextrin (8.2 ), [8] so that if the two a-CDs were to sit over adjacent alkynes, one of them would be pushed over a 2 , TPPTS, CuI, Na 2 CO 3 , H 2 O; solid phase: 6 a, a-CD, Pd(OAc) 2 , TPPTS, CuI, Na 2 CO 3 , H 2 O, then LiOH. [15] bulky phenylene residue.…”
mentioning
confidence: 99%
“…[8] The challenge in translating this chemistry onto a solid support is to find a support that is compatible with the aqueous cyclodextrin-threading process. We chose controlled-pore glass because it has large rigid pores which should provide a suitable environment for aqueous host-guest chemistry, in contrast to solvent-swollen gels, which tend to exclude high-molecular-weight solutes, such as cyclodextrins.…”
mentioning
confidence: 99%
See 2 more Smart Citations